Intelligent interference management in 5G wireless networks - Jiandong LI; Lei LIU; Min SHENG; UChao X (Dianxin kexue)
As one of the key technologies in 5G networks，ultra-dense wireless network is utilized to approach the future 1 000 ultra-high traffic volume.Nevertheless，the dense deployment of network nodes would result in severe interference，and thus interference management was proposed as the big principle behind 5G ultra-dense wireless networks research.Firstly，the interference management schemes were classifed from two aspects：avoidance and utilization.Then，an intelligent interference management architecture was proposed to accommodate the development trend of future wireless networks in terms of intelligence and heterogeneity in order to realize the dynamic tightly coupled interference management of wireless network environment and interference management.Taking the intrinsic relationship between interference management and resource management into consideration，three cutting-edge interference management schemes were introduced，which could significantly improve the network resource utilization and the network capacity.